2006
DOI: 10.1108/02640470610660378
|View full text |Cite
|
Sign up to set email alerts
|

How researchers are using the OPAC of the Spanish Council for Scientific Research Library Network

Abstract: Purpose-The importance of online public access catalogues (OPACs) has changed in recent years, mainly due to the large number of electronic resources now available. The aim of this study is to learn about and evaluate the use made by researchers of the OPAC of the library network of the Spanish Council for Scientific Research, the largest research institution in Spain. Design/methodology/approach-To this end a questionnaire was drafted with questions pertaining both to the system and to the users themselves. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
4
8
0
Order By: Relevance
“…This finding indicates that as perceived ease of use increases, satisfaction with DL will also increase. This finding is also in tandem with Ortiz-Repiso et al (2006), Roca et al (2006), Glerum (2007), Islam (2011) and Yu et al (2012). As stated earlier, ease of use means the DL is easily accessible.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This finding indicates that as perceived ease of use increases, satisfaction with DL will also increase. This finding is also in tandem with Ortiz-Repiso et al (2006), Roca et al (2006), Glerum (2007), Islam (2011) and Yu et al (2012). As stated earlier, ease of use means the DL is easily accessible.…”
Section: Discussionsupporting
confidence: 68%
“…In other studies, Islam (2011) and Glerum (2007) also found that perceived ease of use is a strong predictor of wireless service satisfaction and radio frequency identification satisfaction. Within the domain of library research, Ortiz-Repiso et al (2006) found that ease of use was associated with satisfaction when online public access catalogue (OPAC). Drawing upon the aforementioned studies, it is also expected that perceived ease of use will have a positive influence on satisfaction.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…These e-resources may be classified and linked to the OPAC in order to provide direct access without going to library shelves, as users only want to get information, instead of finding out sources of information. Ortiz-Repiso et al (2006) noted that users broadly used the OPACs not only for finding print resources, but also for the material in electronic format subscribed by the library. Thus, the present study will benefit the library community by enabling those in the library to understand users' problems and expectations for the effective utilization of the OPAC in the internet age, especially in developing countries like India.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Using Type (1) URLs in your OPAC has the advantage of link stability, and conform to the patterns of user demand found in studies of hyperlinked OPACs by recent writers investigating Burke et al 's criticism of OPAC URL management practice. They have found that readers use hyperlinked OPACs “for connecting to the electronic resources subscribed to by the library” (Ortiz‐Repiso et al , 2006), rather than for free web sites offered on the open internet.…”
Section: Urls In the Opac: Uk Practice Focussing On Scotlandmentioning
confidence: 99%